Characterization of GABAergic marker expression in prefrontal cortex in dexamethasone induced depression/anxiety model - Hu, Ling; Qiu, Ming-Jing; Fan, Wen-Juan; Wang, Wan-Er; Liu, Shao-Hao; Liu, Xiao-Qi; Liu, Shi-Wei; Shen, Ze-Jin; Zheng, Ya-Fei; Liu, Guang-Chao; Jia, Zi-Yi; Wang, Xiao-Qing; et al. (Frontiers in Endocrinology, 2024)
The pivotal responsibility of GABAergic interneurons is inhibitory neurotransmission; in this way, their significance lies in regulating the maintenance of excitation/inhibition (E/I) balance in cortical circuits. An abundance of glucocorticoids (GCs) exposure results in a disorder of GABAergic interneurons in the prefrontal cortex (PFC); the relationship between this status and an enhanced vulnerability to neuropsychiatric ailments, like depression and anxiety, has been identified, but this connection is still poorly understood because systematic and comprehensive research is lacking. Here, we explored the impact of dexamethasone (DEX, a GC receptor agonist) on GABAergic interneurons in the PFC of eight-week-old adult male mice. In a depression/anxiety model generated by chronic DEX treatment, we found that the expression levels of a GABA-synthesizing enzyme (GAD67), Reelin, calcium-binding proteins (parvalbumin and calretinin) and neuropeptides co-expressed in GABAergic neurons (somatostatin, neuropeptide Y and vasoactive intestinal peptide) in the PFC were reduced after 21 days of DEX treatment; these reductions were accompanied by decreases in brain size and cerebral cortex thickness. Our results indicate that a reduction in the number of GABAergic interneurons may result in deficiencies in cortical inhibitory neurotransmission, potentially causing an E/I imbalance in the PFC; this insight suggests a potential breakthrough strategy for the treatment of depression and anxiety.